INTRODUCTION OF PRESCHOOL CHILDREN TO EXAMPLES OF FOLK FOLKLORE PERFORMANCE. - Weng Wai Ming (International Journal of Literature and Language Studies, 2022)
This article highlights the importance and methods of introducing preschool children to folk folklore performance. The role of folklore in developing children’s speech, thinking, and moral qualities is analyzed.